Epidemiology of Pediatric Tuberculosis and Factors Associated with Unsuccessful Treatment Outcomes in the Centre Region of Cameroon: A Three-Year Retrospective Cohort Study. (24th August 2022) - Vukugah, Thomas Achombwom; Akoku, Derick Akompab; Tchoupa, Micheline Mekemnang; Lambert, Edward
Abstract : Background . In Cameroon, there are limited data on treatment outcomes of pediatric tuberculosis (TB). We sought to identify the factors associated with unsuccessful treatment outcomes and the risk factors for mortality among children receiving TB treatment in the Centre Region of Cameroon. Methods . This was a multicentre facility-based retrospective cohort study using routinely collected programmatic data. All children <15 years old treated for TB between 2018 and 2020 in 21 health facilities were included. We assessed risk factors for experiencing an unsuccessful treatment outcome and mortality through multivariable logistic regression analysis. Results . Of the 610 children with TB, 307 (50.3%) were females and the median age was 6 years (IQR = 2–12). One hundred and fifty-three (25.1%) of the children were TB/HIV co-infected patients. TB treatment success (cases categorized as cured and completed treatment) was observed in 488 (80.0%) of the patients. Unsuccessful treatment outcomes were experienced by 122 (20.0%) children. Of these, 73 (12.0%) died, 4 (0.6%) had treatment failure, 25 (4.1%) were lost to follow-up, and the outcomes of 20 (3.3%) children were not evaluated. In multivariable analysis, HIV-positive status (adjusted odds ratio [AOR] = 2.43; 95% CI, 1.55–3.80, p < 0.001 ) and clinical method of TB diagnosis (AOR = 2.46; 95% CI, 1.55–3.91, p < 0.001 ] were associated with unsuccessful treatment outcomes. HIV-positive status (AOR = 4.23; 95% CI, 2.44–7.33, p < 0.001 ) and clinical method of TB diagnosis (AOR = 2.22; 95% CI, 1.25–3.91, p = 0.006 ) were the risk factors for mortality among children on TB treatment. Conclusion . The study found that HIV-TB co-infected children and those clinically diagnosed with TB were significantly more likely to have had unsuccessful TB treatment outcomes and mortality. Our findings underscore the need for healthcare workers to closely monitor and support HIV-TB co-infected children on TB treatment. TB/HIV collaborative activities should be strengthened by implementing TB preventive interventions among HIV-infected children.